Effect of relaxin‐3 on Kiss‐1, gonadotropin‐releasing hormone, and gonadotropin subunit gene expression. (5th September 2019) - Kanasaki, Haruhiko; Tumurbaatar, Tuvshintugs; Tumurgan, Zolzaya; Oride, Aki; Okada, Hiroe; Kyo, Satoru
Abstract: Purpose: Relaxin‐3 is a hypothalamic neuropeptide that belongs to the insulin superfamily. We examined whether relaxin‐3 could affect hypothalamic Kiss‐1, gonadotropin‐releasing hormone (GnRH), and pituitary gonadotropin subunit gene expression. Methods: Mouse hypothalamic cell models, mHypoA‐50 (originated from the hypothalamic anteroventral periventricular region), mHypoA‐55 (originated from arcuate nucleus), and GT1‐7, and the mouse pituitary gonadotroph LβT2 were used. Expression of Kiss‐1, GnRH, and luteinizing hormone (LH)/follicle‐stimulating hormone (FSH) β‐subunits was determined after stimulation with relaxin‐3. Results: RXFP3, a principle relaxin‐3 receptor, was expressed in these cell models. In mHypoA‐50 cells, relaxin‐3 did not exert a significant effect on Kiss‐1 expression. In contrast, the Kiss‐1 gene in mHypoA‐55 was significantly increased by 1 nmol/L relaxin‐3. These cells also express GnRH mRNA, and its expression was significantly stimulated by relaxin‐3. In GT1‐7 cells, relaxin‐3 significantly upregulated Kiss‐1 expression; however, GnRH mRNA expression in GT1‐7 cells was not altered. In primary cultures of fetal rat neuronal cells, 100 nmol/L relaxin‐3 significantly increased GnRH expression. In pituitary gonadotroph LβT2, both LHβ‐ and FSHβ‐subunit were significantly increased by 1 nmol/L relaxin‐3. Conclusions: Our findings suggest that relaxin‐3 exerts its effect by modulating the expression of Kiss‐1, GnRH, and gonadotropin subunits, all of which are part of the hypothalamic‐pituitary‐gonadal axis. Abstract : Relaxin‐3 may exert its effect by modulating the expression of Kiss‐1, GnRH, and gonadotropin subunits, all of which are part of the hypothalamic‐pituitary‐gonadal axis.